Local Translation in Axons: When Membraneless RNP Granules Meet Membrane-Bound Organelles - Pushpalatha, Kavya Vinayan; Besse, Florence (Frontiers in Molecular Biosciences, 2019)
The importance and prevalence of membraneless organelles have established liquid-liquid phase separation as a central process underlying cellular organization and compartmentalization. In this review, we highlight how membraneless ribonucleoprotein (RNP) organelles in fact interact with membrane-bound organelles for tight spatio-temporal control of gene expression, using local translation in the axons of neuronal cells as a paradigm. Specifically, we present emerging evidence that motile membrane-bound organelles are used as vehicles by RNP cargoes, promoting the long-range transport of mRNA molecules to distal axons. As demonstrated by recent work, membrane-bound organelles also promote local protein synthesis, by serving as platforms for the local translation of mRNAs recruited to their outer surface. Dynamic and specific association between RNP cargoes and membrane-bound organelles is mediated by bi-partite adapter molecules that interact with both types of organelles specifically, in a regulated-manner. Maintaining such a dynamic interplay is critical, as alterations in this process are linked to neurodegenerative diseases. Together, emerging studies thus point to the coordination of membrane-bound and membraneless organelles as an organizing principle underlying local cellular responses.